2016
DOI: 10.1080/13691058.2015.1134811
|View full text |Cite
|
Sign up to set email alerts
|

From first love to marriage and maturity: a life-course perspective on HIV risk among young Swazi adults

Abstract: This paper uses a life-course approach to explore the sexual partnerships and HIV-related risk of men and women in Swaziland throughout their adolescence, their 20s and 30s. Twenty-eight Swazi men and women between the ages of 20 and 39 discussed their life histories in 117 in-depth interviews, with an average follow-up of 9 months. Many participants reported painful childhood experiences, including a lack of positive role models for couple relationships. Women’s first sexual partnerships often involved coerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The historical and economic reasons for the decline in marriage across southern Africa are beyond the scope of this paper, but the critical point is that while marriage remains a widespread aspiration in Swaziland (Ruark et al, 2016), many Swazis are not married or in a marriage-like relationship. According to the most recent Demographic and Health Survey (2006–07), the median age at first marriage was 24 among women and 28 for men.…”
Section: Introductionmentioning
confidence: 99%
“…The historical and economic reasons for the decline in marriage across southern Africa are beyond the scope of this paper, but the critical point is that while marriage remains a widespread aspiration in Swaziland (Ruark et al, 2016), many Swazis are not married or in a marriage-like relationship. According to the most recent Demographic and Health Survey (2006–07), the median age at first marriage was 24 among women and 28 for men.…”
Section: Introductionmentioning
confidence: 99%
“…However, for women with less constrained agency in their relationships, the decision to forgo condoms with a sexual partner may be made based on personal preferences, and the decision is more likely to be made with agency, affection and trust. For many couples in Swaziland, southern Africa and the rest of the world, gift giving and financial support from a male partner are normative parts of courtship and relationships [ 13 , 26 , 64 , 65 ]. Research across the globe has shown that as intimacy and trust in a relationship increases, condom use decreases even in contexts with a high background HIV prevalence [ 66 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies aimed at understanding these experiences, for example, have focused on sexual risk because of HIV, a disease disproportionately affecting young South African women (e.g., Idele et al 2014; Ruark et al 2016; Shisana et al 2014). The risk of unintended pregnancy and the lack of contraception are also common subjects of concern (e.g., Christofides et al 2014; Harrison et al 2016; Mchunu et al 2012), as is the culture of sexual- and gender-based violence in South Africa (e.g., Jewkes et al 2010; Russell et al 2014; Waxman et al 2016).…”
Section: Introductionmentioning
confidence: 99%